2022
DOI: 10.1186/s13018-021-02907-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between external locking plate fixation and conventional external fixation for extraarticular proximal tibial fractures: a finite element analysis

Abstract: Background Good clinical outcomes for locking plates as an external fixator to treat tibial fractures have been reported. However, external locking plate fixation is still generally rarely performed. This study aimed to compare the stability of an external locking plate fixator with that of a conventional external fixator for extraarticular proximal tibial fractures using finite element analysis. Methods Three models were constructed: (1) external … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In recent years, with the development of computer image processing technology, finite element analysis has been applied to various fields, which has greatly promoted the development of bio-medicine [ 28 ]. The emergence of finite element analysis provides a new idea for the study of biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the development of computer image processing technology, finite element analysis has been applied to various fields, which has greatly promoted the development of bio-medicine [ 28 ]. The emergence of finite element analysis provides a new idea for the study of biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…These models were constructed using computer assisted design (CAD) and analyzed using FEA. They found higher stiffness in models with conventional external fixators [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marti et al were the first to use an internally fixed tibial anatomic locking splint as an external fixator in 1984 to treat open fractures, infected bone discontinuity, septic arthritis and other related conditions [15,18]. Subsequent finite element analysis and biomechanical studies on the stability of LCP external fixators for tibial fractures have shown that LCP has good biomechanical stability as an external fixator [19][20][21][22][23][24][25][26]. At the same time, some scholars have also applied LCP in clinical practice to treat open tibial fractures and have obtained more satisfactory results in clinical practice [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%